Associations of cardiovascular risk factors with handgrip strength and gait speed among older males and females: A systematic review protocol - Allen Suzane de França; Amanda Silva Saldanha; Alex Moreira da Silva; Catherine M Pirkle; Ana Tereza do Nascimento Sales Figueiredo Fernandes; Saionara Maria Aires da Câmara (PLoS ONE, 2026)
Introduction Cardiovascular risk factors (CRFs), such as hypertension, diabetes, dyslipidemia, and smoking are associated with several adverse health outcomes among older people, such as poor physical function. Handgrip strength and gait speed are key measures of physical function that indicate general health status among older people. Nevertheless, it is unclear which factors have the greatest impact on these measures in older adults. In addition, gender differences in cardiovascular disease risk are observed, with older women with a history of diabetes, obesity, and hypertension being more prone to cardiovascular events than older men. This may be related to different patterns of cardiovascular aging, which may impact the physical function of older men and women differently over time. This article aims to describe the protocol for a systematic review to identify which CRFs are associated with measures of physical function (handgrip strength and gait speed) and whether this association varies by sex. Methods and analysis A systematic search will be conducted in the PubMed, LILACS (Latin American and Caribbean Health Sciences Literature), Cochrane Library, Web of Science and Embase databases. The sorting and tracking of articles will be performed with the help of the Rayyan platform. Following the recommendations of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P), the main reviewer will conduct the initial search and exclusion of duplicates, and two researchers will extract data from the selected articles independently and blindly, using an instrument built specifically for this research. Discrepancies will be solved by a third reviewer. Cross-sectional and/or longitudinal studies, involving community-dwelling older individuals and that have assessed the association between CRFs and measures of physical function (handgrip strength and/or gait speed) will be included. The methodological quality of the included studies will be assessed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. PROSPERO registration number CRD420251167299.